Mortality in systemic vasculitis: a systematic review. - Phillip, R; Luqmani, R (2008)
There has been a considerable improvement in the survival of patients with systemic vasculitis since the introduction of immunosuppressive therapy and improved diagnostic tools to allow earlier diagnosis. We review the published literature on current risk of mortality in patients with small vessel antineutrophil cytoplasm antibody- (ANCA) associated vasculitis including Wegener's granulomatosis (survival rate of approximately 75% at 5 years), microscopic polyangiitis (survival rate of 45% to 75% at 5 years), Churg-Strauss syndrome (survival rate of 68% to 100% at 5 years), and Henoch-Schönlein purpura (survival rate of 75% in adult-onset, greater in childhood onset); medium vessel vasculitis including polyarteritis nodosa (survival rate of 75% to 80% at 5 years), Kawasaki disease (survival rate of greater than 99% at 5 years); large vessel vasculitis including giant cell arteritis (survival rate equivalent to the age-matched population), and Takayasu arteritis (survival of 70% to 93% at 5 years). Mortality rates are falling as a result of more effective intervention but remain elevated substantially in severe disease. Early deaths are usually attributable to active vasculitis with multiorgan failure or infection, or both. The incidence of late deaths may be increased by long-term effects of therapy and development of comorbidities. These findings highlight the need to improve early diagnosis and initiation of targeted therapy, thereby reducing treatment-related toxicity and comorbidities.